Ekeland-type variational principle with applications to nonconvex minimization and equilibrium problems - Iqbal, Iram; Hussain, Nawab (Nonlinear Analysis: Modelling and Control, 2019)
The aim of the present paper is to establish a variational principle in metric spaces without assumption of completeness when the involved function is not lower semicontinuous. As consequences, we derive many fixed point results, nonconvex minimization theorem, a nonconvex minimax theorem, a nonconvex equilibrium theorem in noncomplete metric spaces. Examples are also given to illustrate and to show that obtained results are proper generalizations.